A highly effective Ni-modified MnOx catalyst for total oxidation of propane: the promotional role of nickel oxide. Issue 55 (23rd May 2016) - Xie, Yujie; Guo, Yun; Guo, Yanglong; Wang, Li; Zhan, Wangcheng; Wang, Yunsong; Gong, Xueqing; Lu, Guanzhong
Abstract : Adding Ni (Ni/Mn of 0.2) into an MnO x catalyst greatly enhanced its catalytic performance for propane total oxidation. Abstract : Nickel promoted manganese oxide (MnNiO x ) was prepared by the co-precipitation method and used as a catalyst for propane deep oxidation. The results show that the doping of Ni can effectively improve the catalytic performance of MnO x for propane total oxidation, and when Ni/Mn is 0.2, the MnNi0.2 O x catalyst exhibits the highest catalytic activity, for instance, the reaction temperature of 90% propane conversion ( T 90 ) was only ∼240 °C, and it demonstrates good thermal stability in the operation at temperatures alternating between 220 °C and 350 °C. It was found that an Mn–Ni–O solid solution can be formed by adding a moderate Ni amount into MnO x, resulting in changes in catalytically active sites by the synergetic interaction of Mn–Ni, such as a higher surface concentration of Mn 4+ and oxygen vacancies, higher oxygen mobility and better reducibility. And the outstanding catalytic property of MnNi0.2 O x can be also related to its high surface area. Furthermore, the in situ DRIFT technique was used to investigate the reaction process of propane oxidation over the MnO x and MnNi0.2 O x catalysts, and the results suggest that the reaction mechanism is hardly changed after Ni doping in MnO x .